Undergraduates' attitudes of writing and views towards mind-mapping as a pre-writing strategy - Roslim, Norwati; Abdullah, Muhammad Hakimi Tew; Mohd Razali, Nornadiah; Mirza, Akhmad Ali; Nimehchisalem, Vahid (Asian Association of Teachers of English As a Foreign Language, 2024)
Writing is said to be challenging and more difficult for learners in a second language academic context (Shakoori et al., 2017). Undoubtedly, lecturers in higher education, teachers in schools as well as students face several challenges in teaching and learning writing. Challenges faced by students include students’ lack of interest, readiness and motivation regarding writing in English (Anyiendah, 2017). Such challenges have made it difficult for lecturers and teachers to teach writing (Moses & Mohamad, 2019). Hence, the need to provide appropriate teaching strategies is essential to stimulate and motivate learners to express and generate their ideas. Several writing strategies have been posed to tackle the challenges faced by lecturers, teachers and students. However, it is the concern of this study to focus on the initial stage of writing that is a pre-writing activity. This is based on the premise that an effective teaching strategy is required to motivate learners to express and generate their ideas in writing at an early stage. Mind-mapping is a technique that is used in the pre-writing activity. It is a “planning activity in the writing that is done by writing key words around the topic” and this is to “expand the students’ ideas into good paragraphs” (Waloyo, 2017, p. 73). Besides, it is “easier for students to write down their ideas that are in their minds into a written work” (Mantra et al., 2021, p. 16). Also, mind maps can work as a tool to facilitate the learners to plan ideas in the pre-writing process (Bukhari, 2016) and can create an enjoyable classroom atmosphere (Sapitri et al., 2019). Mind maps that are applied as a pre-writing activity are said to enhance the content and organization of written outputs (Sebit & Yildiz, 2020).